Heft Peyker Mesnevis in Turkish literature and Hayâtî’s Heft Peyker - Sürelli, Bahadır. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2012., 2012)
Starting from the question of how the Bahram Gor narratives have emerged in Persian literature, this work researches a sixteenth century Divan poet Hayâtî’s Haft Paykar, in terms of the dispersion of the subject to Anatolian field and examines how the Turkish writers has approached to these narratives. Therefore this thesis has many folds to make it clear. First of all, it should be determined that the historical personality of Sasanian king Bahram V whose life has been told as a legend in both Persian and Turkish literatures, and then we need to find the legendary narrative sources which his life has been nourished from. Hence, we will try to point out what are the sources that the story identified with, and how old are these stories. On the other hand, with a comperative analysis, it is aimed that the story of Bahram which was first in Persian then Turkish, how and by which poets has been told in literary works since Firdausi. As a chain linked between first with Firdausi, Nizami, Hosrau, and Ali Shir Navai and then with the other poets- the journey and the evolution of Bahram romance could have been followed. The other poets, translated Haft Paykar into Turkish until the time when Hayati wrote his Haft Paykar, have also been added to this process and all analized historically together. Another goal is to realize the most common features of the Haft Paykar texts and realize the new dimensions could been observed in the hands of each. Last of all, we tried put stress on Hayati’s text in terms of its unique features, language, and style. Due to the two existing manuscripts of the work we tried to determine the critical edition of the text as well.
Keywords: Persian literature -- Translations into Turkish.; Persian poetry.